Development Of Thesis Repository Application In The Faculty Of Science And Technology Use Implementation Of Vue.Js Framework - Irhansyah, Teddy; Padli Nasution, M.Irwan; Triase (Ali Institute or Research and Publication, 2023)
Information technology can be utilized in the world of education as a means of conveying information about the profile of an institution, as a means of facilitating the running of government, and as a means of supporting other academics. UIN North Sumatra, especially the Faculty of Science and Technology, does not yet have information technology that can store student thesis data, where the application can be used as a search tool for theses that have been published within the Faculty of Science and Technology. By storing thesis manuscripts electronically, it will also make it easier to track the track record of each student and lecturer in preparing the thesis. Through the electronic thesis data storage application, the lecturers and thesis students can find out what titles have been published so that they can be used as indicators of what science is currently developing in the Faculty of Science and Technology. Based on the thesis data stored in an application, later this data can also be used for accreditation or academic purposes. Making this system researchers use the Vue.js Framework which is a flexible framework, Vue.js can be integrated with other frameworks or libraries such as Django, Laravel and WordPress. By implementing the Vue.js framework in website-based application development, the website can be embedded with one-page application features so that it will be easier to use the application.